(3H)hemicholinium-3 binding sites in postmortem brains of human patients with Alzheimer's disease and multi-infarct dementia - Kristofiková, Z; Fales, E; Majer, E; Klaschka, J (Experimental gerontology, 1995)
(3H)Hemicholinium-3 ((3H)HCh-3), a potent, selective, and competitive inhibitor of the high-affinity choline uptake process was used for the detection of high-affinity choline carriers in the hippocampus (gyrus parahippocampalis), neocortex (gyrus frontalis medius), and cerebellum (lobulus semilunaris inferior) in autopsy samples of people with Alzheimer's disease, multi-infarct dementia and from other psychiatric and nonpsychiatric patients. The effect of postmortem delay was eliminated by means of the cerebellum used as an individual standard. The density of (3H)HCh-3 binding sites was decreased in the hippocampus and neocortex from individuals with multi-infarct dementia and unchanged in the brain tissue from people with Alzheimer's disease in comparison with control patients. No changes in dissociation constants were found. In Alzheimer's disease, high-affinity choline transport appears to be reduced by a dysfunction of cholinergic neuronal membrane rather than by a significant decrease in the number of presynaptic cholinergic nerve terminals. Results provide evidence of a decrease in the number of nerve endings in people with multi-infarct dementia and suggest different vulnerability of particular brain areas to vascular disorders.
Keywords: Alzheimerova nemoc; Dementia, Multi-Infarct; Hemicholinium 3; tritium; Autopsy; senioři; Binding, Competitive; Aged; Male; lidé; Analysis of Variance; lidé středního věku; Humans; multiinfarktová demence; Tritium; Middle Aged; pitva; Binding Sites; senioři nad 80 let; Aged, 80 and over; mužské pohlaví; analýza rozptylu; Choline; kompetitivní vazba; vazebná místa; hemicholinium 3; Case-Control Studies; ženské pohlaví; cholin; Alzheimer Disease; Female; studie případů a kontrol